A rare case of chondrosarcoma arising in parotid with extension to lateral skull base. Issue 12 (2nd December 2019) - Pradhan, Sidharth; Sarkar, Saurav; Sable, Mukund N; Parida, Pradipta Kumar
Abstract : Chondrosarcomas of head and neck region are rare. Very few cases of chondrosarcomas arising in parotid gland have been reported and none with intracranial extension. We report a case of a female presenting with a parotid swelling and a mass in external auditory canal with extradural extension to posterior cranial fossa. With a preoperative fine needle aspiration diagnosis of pleomorphic adenoma, it was excised and the histopathology came out to be low-grade myxoid chondrosarcoma. She has not received any adjuvant chemoradiotherapy and there is no evidence of recurrence at months.